Assessment of Long-Term Land Cover Changes and Urban Expansion in Cities of the Hungarian Great Plain Using CORINE Data and Historical Maps - Dávid Balázs; István Fazekas; Tamás Mester (Land)
Increasing anthropogenic disturbance in urban areas and the expansion of built-up zones into surrounding rural landscapes represent one of the most significant spatial and ecological challenges of recent decades. Urban expansion influences not only land use patterns but also the ecological integrity and naturalness of the landscape. In the present study, anthropogenic landscape change trends and changes in land cover categories were investigated within the current administrative boundaries of Nyíregyháza, a county seat located in northeastern Hungary. Using data from the CORINE Land Cover program (1990, 2000, 2012, 2018) and historical military surveys (1819–1869), landscape development trends within the municipality were examined over the past one and a half centuries. Particular attention was focused on examining changes in the extent of built-up areas, which are among the most concerning from a landscape ecological perspective. By comparing the results with data from other Hungarian cities (Debrecen and Szeged), a significant increase—nearly 20%—in built-up areas was identified. The proportion of built-up areas in relation to the total municipal administrative area increased in all the periods studied, even in those where the population was decreasing. This indicates that even in municipalities experiencing demographic decline, internal population redistribution may lead to the spatial growth of certain neighborhoods, which are the primary contributors to the expansion of built-up urban areas. Finally, based on CORINE Land Cover data, the ecological conditions of Nyíregyháza were assessed, and a hemeroby map of the municipality was created, reflecting landscape changes that occurred between 1990 and 2018. It was found that over a 28-year period, the total area of the most ecologically problematic meta- and polyhemerobic categories increased by 6%, in parallel with the growth of built-up areas.